Enhancement of CO2 and Toluene Adsorption on a Rare‐Earth Chalcophosphate Aerogel by Post Synthetic Modification with PdCl2. Issue 14 (7th July 2019) - Edhaim, Fatimah; Rothenberger, Alexander
Abstract : The sol‐gel metathesis reaction was used to synthesize a new family of aerogels called a rare‐earth chalcophosphate aerogel KY(P2 S6 )2 · K + and the rare‐earth metal cations Y 3+ connect [P2 S6 ] 2– anions to form an amorphous white gel. Supercritical drying of the resulting gel produced porous materials with a BET surface area of 443 m 2 · g –1 . The adsorption properties of the rare‐earth chalcophosphate aerogel were studied using volatile organic hydrocarbons (VOCs) and gases as adsorptives. The results showed preferential adsorption of toluene vapor over cyclohexane and cyclopentane vapor. The adsorption capacity toward toluene was 703 mg· g –1 . Favored adsorption of CO2 over CH4, N2, or H2 was also observed for the aerogel: KY(P2 S6 )2 (CO2 /H2 : 308, CO2 /CH4 : 67, Co2 /N2 : 177). Pd doped aerogel showed significant enhancement toward toluene (1291 mg· g –1 ) for 1 wt % Pd @ KY(P2 S6 )2, (2064 mg· g –1 ) for 3 wt % Pd @ KY(P2 S6 )2 and (1108 mg· g –1 ) for 5 wt % Pd @ KY(P2 S6 )2 . It also showed a noticeable improvement in the gas selectivity (CO2 /H2 : 337, CO2 /CH4 : 85, Co2 /N2 : 205) for 1 wt % Pd @ KY(P2 S6 )2, (CO2 /H2 : 345, CO2 /CH4 : 109, Co2 /N2 : 212) for 3 wt % Pd @ KY(P2 S6 )2 and (CO2 /H2 : 319, CO2 /CH4 : 73, Co2 /N2 : 187) for 5 wt % Pd @ KY(P2 S6 )2 . Abstract :